High dosage of Exendin-4 increased early insulin secretion in differentiated beta cells from mouse embryonic stem cells - Li Hua; Lam Amy; Xu Ai-min; Lam Karen Sl; Chung Sookja Kim (Acta Pharmacologica Sinica; Vol 31, No 5 (May 2010): Acta Pharmacologica Sinica, 2016)
Aim: To investigate early insulin release (EIR) and late insulin release (LIR) upon glucose challenge as well as important insulin signaling factors in differentiated insulin-producing cells from embryonic stem cells(ESCs). Methods: A recently published protocol was modified by increasing the concentration of Exendin-4 (from 0.1 nmol/L to 10 nmol/L) together with an additional 5-day culture in low glucose (5.5 mmol/L) medium after differentiation. Gene expression profile, insulin content, C-peptide, EIR and LIR were determined. Results: Compared to a lower concentration of Exendin-4 (0.1 nmol/L), a higher concentration of Exendin-4 (10 nmol/L) increased glucose-responsive insulin secretion, especially EIR. Moreover, 10 nmol/L Exendin-4 increased the expression of the following genes: insulin 1, Pdx-1 (an important transcription factor, newly recognized insulin signaling factors), Epac1 and Epac2 (exchange proteins directly activated by cAMP 1 and 2), and sulfonylurea receptor 1 (SUR1, the subunit of the KATP channel). Conclusion: According to current knowledge, our modified protocol with a higher concentration of Exendin-4 (10 nmol/L) together with an additional 5-day 5.5 mmol/L glucose culture after differentiation improved the efficiency of differentiation toward the beta cell phenotype, which was possibly the result of stimulated expression of Pdx-1, Epac 1, and Epac 2, which in turn inhibited the K(ATP) channel through combination with SUR1, leading to increased EIR upon glucose challenge.